Plan de negocios del proyecto Hotel Rehabilipar (2021)
The project aims to contrition the Hotel Rehabilipar, in the Palomino la Guajira sector, an area that has taken on a lot of tourist influx in recent years, the differential factor of this hotel is that it is a center for the integration of heterosexual couples or the LGTBI community, We also seek to be pioneers in Adults Only, a hotel theme based on the reception of adults, it should be noted that single people cannot go to the place either.